Predictors of psychiatric hospitalization among outpatients with bipolar disorder in the real-world clinical setting - Tokumitsu, Keita; Yasui-Furukori, Norio; Adachi, Naoto; Kubota, Yukihisa; Watanabe, Yoichiro; Miki, Kazuhira; Azekawa, Takaharu; Edagawa, Koji; Katsumoto, Eiichi; Hongo, Seiji; Goto, Eiichiro; Ueda, Hitoshi; et al. (Frontiers in Psychiatry, 2023)
Background: Bipolar disorder is a psychiatric disorder that causes recurrent manic and depressive episodes, leading to decreased levels of social functioning and suicide. Patients who require hospitalization due to exacerbation of bipolar disorder have been reported to subsequently have poor psychosocial functioning, and so there is a need to prevent hospitalization. On the other hand, there is a lack of evidence regarding predictors of hospitalization in real-world clinical practice. Methods: The multicenter treatment survey on bipolar disorder (MUSUBI) in Japanese psychiatric clinics was an observational study conducted to provide evidence regarding bipolar disorder in real-world clinical practice. Psychiatrists were asked, as part of a retrospective medical record survey, to fill out a questionnaire about patients with bipolar disorder who visited 176 member clinics of the Japanese Association of Neuro-Psychiatric Clinics. Our study extracted baseline patient characteristics from records dated between September and October 2016, including comorbidities, mental status, duration of treatment, Global Assessment of Functioning (GAF) score, and pharmacological treatment details. The incidence and predictors of hospitalization among patients with bipolar disorder over a one-year period extending from that baseline to September-October 2017 were examined. Results: In total, 2389 participants were included in our study, 3.06% of whom experienced psychiatric hospitalization over the course of one year from baseline. Binomial logistic regression analysis revealed that the presence of psychiatric hospitalization was correlated with bipolar I disorder, lower baseline GAF scores, unemployment, substance abuse and manic state. Conclusions: Our study revealed that 3.06% of outpatients with bipolar disorder were subjected to psychiatric hospitalization during a one-year period that extended to September-October 2017. Our study suggested that bipolar I disorder, lower baseline GAF scores, unemployment, substance abuse and baseline mood state could be predictors of psychiatric hospitalization. These results may be useful for clinicians seeking to prevent psychiatric hospitalization for bipolar disorder.